Calcium Phosphate From Waste Animal Bones:Phase Identification Analysis - Abd Rahim, Toibah; Misran, F.; Mustafa, Zaleha; Shaaban, Azizah; Shamsuri, Siti Rahmah (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
Calcium phosphate bioceramic forms are widely being developed in biomedical applications due to their excellent biocompatibility,bioactivity and osteoconduction characteristics.Apart from synthesized from egg shell wastes,calcium phosphates can be extracted from animal bones.In this study,natural calcium phosphate was extracted by calcination of three different animal bones,which are cow (bovine),goat (caprine) and chicken (galline).The crystallinity and phase identification from FTIR spectrum and XRD patterns were discussed in this paper.Calcium phosphate structures were confirmed through the presence of PO4 3- and OH- bands as observed by FTIR analysis.FTIR spectra also showed that the organic substances are eliminated in the as-calcined bones at 1000°.XRD results revealed that the as-calcined bones were biphasic calcium phosphate which was verified with relative intensity ratio.The crystallite sizes of the extracted calcium phosphates were estimated to be less than 90nm.Moreover,this study revealed that caprine bones showed the highest HA phase present,followed by bovine and galline bones.